Performance level and cardiopulmonary responses during a cycle-run trial - Hue, O.; Le Gallais, D.; Boussana, A.; Chollet, D.; Prefaut, C. (International Journal of Sports Medicine, 2000)
To determine the effect of triathlete performance level on the cardiorespiratory responses elicited by the cycle-run succession, eight regionally and nationally-ranked (Competitive) and five internationally-ranked (Elite) male triathletes underwent four successive laboratory trials: 1) an incremental treadmill test, 2) an incremental cycle test, 3) 30 min of cycling followed by 20 min of running (C-R), and 4) a 20-min control run (R) at the same speed as the run in C-R. Before and 10 min after the third and fourth trials the triathletes underwent lung function testing: spirometry and diffusing capacity testing for carbon monoxide (DL(CO)). During the C-R trial blood samples were drawn to measure venous lactate concentration. During all trials ventilatory data were collected every minute using an automated breath-by-breath system. The results showed that 1) the oxygen uptake (VO2) of post-cycling running versus running alone was similar for both groups; 2) the ventilatory responses (VE, VE/VO2, VE/VC02 and f) of C-R running versus R were significantly higher (P < 0.005) for the Competitive group; and 3) a significant decrease (P< 0.05) in DL(CO) was also noted after the C-R trial in the Competitive group but not in the Elite group. We concluded that 1) the ventilatory responses during a run subsequent to cycling may be related to the triathlete performance level, and 2) the C-R trial induced specific alterations in pulmonary function that may be associated with respiratory muscle alteration and exercise-induced hypoxemia in the Competitive triathletes.